PENGARUH KOMISARIS INDEPENDEN DAN KARAKTERISTIK KOMITE AUDIT TERHADAP INTERNET FINANCIAL REPORTING DISCLOSURE - Rudi Zulfikar (Universitas Muhammadiyah Metro, 2018)
AbstractThis Study aimed to analyze the influence of the proportion of Independent Commisioner and the characteristic Audit Committee to internet financial reporting disclosure. Proportion of Independent Commissioner measured by the ratio of owned Independent Commissioner to Board of Commisioner. Characteristic of the Audit Committee is proxed by the size, AUdit Committe's meeting frequency. The Audit Committee expertise in accounting / financial and the independent parties of the Audit Committee's proportion. Internet financial reporting disclosure is measured by the disclusre items required under the Bank Indonesia Regulation No. 7/50/PBI/2005. The sample in this research were 90 companies and samples used in this study were companies listed in Bank Indonesia during the years 2011- 2014. Statistical method used multiple regression analysis. Based on the test result show that the Proportion of Independent Commissioner had no efect to Internet financial reporting disclosure. And then, Characteristic of the Audit Committee comprimised of several prixies which are size of the Audit Committe, Audit committee meeting frequency, AUdit Commimittee expertise in financial / accounting and independent parties of the Audit Committee had a positive and significant effect to the internet financial reporting disclosure. Size as control variabel had a positive and significant effect to the internet financial reporting disclosure.